1990
DOI: 10.1037/0022-0663.82.4.657
|View full text |Cite
|
Sign up to set email alerts
|

Academic, social, and general self-concepts of behavioral subgroups of learning disabled children.

Abstract: This study assessed perceived competence in 60 children, aged 8 to 13 years, who were classified into 4 carefully matched groups: (a) non-learning-disabled (non-LD), non-behavior-disordered, (b) LD, non-behavior-disordered, (c) LD with externalizing symptoms, and (d) LD with externalizing and internalizing symptoms. Results indicated that the scores of the non-behavior-disordered groups were higher than those of the behavior-disordered groups in cognitive, social, and general self-concept. The scores of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
9

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 48 publications
(70 reference statements)
1
22
0
9
Order By: Relevance
“…Moreover, Zeleke's (2004) metaanalytic review found that 70% of 30 reported studies found no significant differences between the social self-concepts of children with learning disabilities and their normally achieving peers, with 20% finding the LD group less socially well adjusted and the remainder finding them socially more adept. Further light is thrown on these confusing messages by the work of Durrant et al (1990), who examined the social and emotional outcomes for different LD subgroups and found that children with comorbid behaviour disorders showed signs of comparatively poor social self-concepts, whereas those without such associated difficulties did not. The important point to be made here is that we cannot assume that all samples of children or adults with dyslexia or learning disabilities share the same characteristics, apart from their specific difficulties.…”
Section: What the Literature Tells Usmentioning
confidence: 97%
“…Moreover, Zeleke's (2004) metaanalytic review found that 70% of 30 reported studies found no significant differences between the social self-concepts of children with learning disabilities and their normally achieving peers, with 20% finding the LD group less socially well adjusted and the remainder finding them socially more adept. Further light is thrown on these confusing messages by the work of Durrant et al (1990), who examined the social and emotional outcomes for different LD subgroups and found that children with comorbid behaviour disorders showed signs of comparatively poor social self-concepts, whereas those without such associated difficulties did not. The important point to be made here is that we cannot assume that all samples of children or adults with dyslexia or learning disabilities share the same characteristics, apart from their specific difficulties.…”
Section: What the Literature Tells Usmentioning
confidence: 97%
“…Children with learning difficulties face frustration not only in learning but also in relationships (Durrant, Cunningham & Voelker, 1990). Filial therapy has been found to promote a more positive and secure relationship between parents and children (B.…”
mentioning
confidence: 99%
“…In addition to the feedback from adults, childrens' self-assessments of competency are increased when they are made aware of succeeding at a task (Stipek & MacIver, 1989). The treatment program enabled the children to succeed academically and socially which, in addition to positive feedback, leads to increased self-competency assessments (Durrant, Cunningham & Voelker, 1990). Another element of the therapeutic intervention that increases self-concept is the frequent positive evaluation of the subject in public (Tice, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Durrant, Cunningham, & Voelker, 1990;Garg, 1992;Marsh & Craven, 1991;Skaalvik, 1990). Academic self-concept has been found to have a positive correlation with academic achievement and other academic behaviors (Garg, 1992;Marsh, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation